VISUAL ISLAMIC PEDAGOGY IN THE DIGITAL AGE: A CASE STUDY OF HIJAIYAH LITERACY COUNSELING USING VIDEO AND POSTER - Indah Munadhifah (INSTITUT AGAMA ISLAM NEGERI METRO, 2025)
This study aims to analyze the effectiveness of animated video and poster media in enhancing hijaiyah literacy among elementary school students. The research was motivated by the low mastery of hijaiyah letters among students at SD Negeri 03 Beji, who had difficulty recognizing and pronouncing the letters due to traditional teaching methods lacking visual and interactive elements. Using a mixed-methods approach involving observations, interviews, and questionnaires, the study found that colorful animated videos, clear pronunciation audio, and strategically placed hijaiyah posters significantly improved student attention, motivation, and participation in Qur’anic learning. The findings also reveal that consistent visual exposure supports the internalization of letter shapes and sounds through repetition and daily interaction. Teachers noted that the media encouraged independent learning and sustained interest beyond formal class sessions. This study contributes to the discourse on Islamic education by emphasizing the importance of technological adaptation in foundational religious instruction. The integration of media in Qur’anic education not only enhances learning outcomes but also offers a relevant, affordable, and replicable pedagogical model suitable for schools with limited resources.